JAMINAN KESEHATAN ACEH (JKA) DAN PENGUATAN SISTEM KESEHATAN DI PROVINSI ACEH - Abdullah, Asnawi (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2011)
Asnami Abdullah, PhD*Dosen Kopertis Wilayah I, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh AbstractMany strategies have been implemented to improve health system performance in Aceh since last five years including improving healthcare infrastructure, human resources capacity and financing systems. Since early June 2010, Government of Aceh has introduced a health insurance scheme called JKA. This study analysed to what extent the JKA scheme could strengthen health system performance in Aceh. The analysis was performed using the World Health Organization (WHO) health system framework. Theoretically, JKA could strengthen health system performance, however the balance of financial risk and incentive among implementers are the key success of program that should be taken into account by stakeholders. The scheme should not only focus on clinical curative services but also promotive and preventive services. Regular supervision and monitoring of impact on accessibility, the quality of care and level of satisfaction both patient and providers are key components of sustainability of scheme.Keywords : JKA, healthcare, health care, health insurance